2011
DOI: 10.1097/ta.0b013e318221aa4c
|View full text |Cite
|
Sign up to set email alerts
|

Decay-Accelerating Factor Mitigates Controlled Hemorrhage-Instigated Intestinal and Lung Tissue Damage and Hyperkalemia in Swine

Abstract: Background Activation of complement system has been associated with tissue injury after hemorrhage and resuscitation in rats and swine. This study investigated whether administration of human recombinant decay-accelerating factor (DAF; a complement regulatory protein that inhibits classical and alternative pathways) reduces tissue damage in a porcine model of hemorrhagic shock. Methods Male Yorkshire swine assigned to four groups were subjected to controlled, isobaric hemorrhage over 15 minutes to a target m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 23 publications
(34 reference statements)
3
27
0
Order By: Relevance
“…Consistent with previous studies (11,55), we showed that complement-depleted mice are also protected from remote lung damage after mesenteric IR. In particular, we demonstrate that intestinal tissue damage is significantly reduced in complement-depleted MRL/lpr compared with complement-sufficient MRL/lpr mice.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies (11,55), we showed that complement-depleted mice are also protected from remote lung damage after mesenteric IR. In particular, we demonstrate that intestinal tissue damage is significantly reduced in complement-depleted MRL/lpr compared with complement-sufficient MRL/lpr mice.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that decayaccelerating factor attenuated C-reactive proteinYenhanced tissue damage in murine mesenteric ischemia/reperfusion (5) and protected neurons from hypoxia-mediated injury in vitro (11). We also found that decay-accelerating factor mitigates hemorrhage-associated intestinal and lung tissue damage and hyperkalemia in a controlled hemorrhage swine model (3).…”
Section: Discussionmentioning
confidence: 87%
“…Treatments are aimed at restoring intravascular volume and maintaining vital organ perfusion (1). Complement activation has been implicated during hemorrhage in rats (8) and swine (3,10) and relates to morbidity and mortality of trauma patients because of severe inflammatory tissue destruction (4). Peckham et al (8) showed that complement inhibition decreased resuscitation fluid requirements of hemorrhaged rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blast overpressure; Complement activation; Decay accelerating factor; Lung; Rat James E Campbell 1 , Thomas Oh 1 , Brady J Hurtgen 1 , Debra M Niemeyer 1 , Forest R Sheppard 2 and Jurandir J Dalle Lucca 1 * integrity, reducing tau phosphorylation and decreasing cytotoxic edema [16]. DAF administration following hemorrhage and/or I/R also has been shown to limit lung and intestine tissue damage, decrease complement activation and tissue deposition, decrease IL-6 production and improve survival chances [17][18][19][20]. We therefore hypothesized that DAF administration would ameliorate pulmonary and intestinal damage commonly produced by blast injury.…”
Section: Introductionmentioning
confidence: 99%